APLIKASI TEKNOLOGI RITX SOIL DAN WEATHER SENSOR DALAM PENINGKATAN PRODUKSI PADI: BAGAIMANA ADOPSI INOVASI PETANI? - Asnamawati, Lina; Eka Herawati, Is; Rasoki, Timbul; Faridha, ida; Nurmalia, Ana (University of Prof. Dr. Hazairin, SH, 2023)
In certain locations of Indonesia, Ritx Soil and Weather Sensor technology has been used in the agriculture industry. However, scientific reports on farmer technology uptake are not publicly available for scientific and policymaking purposes. As a result, this study was conducted to give scientific data on the acceptance of farmer technological advancements. This exercise was conducted in Cikembulan Village, Garut Regency, with 56 participants. According to the report, only 41% of respondents used technology. Cosmopolitanism, farmer motivation, farmer presence, self-efficacy, the function of extension personnel, frequency of extension, education, and farm experience are the elements of innovation adoption explored. Only farm experience has a favorable impact on the uptake of farmer innovations. Finally, there must be a significant push, particularly from the non-profit organizations and the government.